PENTINGNYA PENYUSUNAN LAPORAN KEUANGAN UNTUK PENILAIAN KINERJA USAHA UMKM DI RW.08 KELURAHAN KAYU PUTIH, PULO GADUNG, JAKARTA TIMUR: The Importance of Preparing Financial Reports for Assessing the Performance of Small Medium Enterprises in RW .08 Kayaputih Kelurahan, Pulo Gadung, East Jakarta - Rina Hartanti; Emma Saur Nauli Sipayung; Hermi Hermi (PUAN INDONESIA, 2023)
The success of MSME (Micro, Small and Medium Entities) entrepreneurs in dealing with the impact of the economic crisis either in 1998 or in 2008/2009 is of course inseparable from the commitment of MSME entrepreneurs themselves to continue to improve the performance of their MSME businesses. Assessment of MSME business performance is very important for MSME entrepreneurs in making strategic business decisions correctly and correctly. The right and correct decision can increase the progress of the MSME business, but on the contrary, wrong decision making can pose a risk of failure of the MSME business.So that the decisions taken by MSME entrepreneurs are not wrong, it is necessary to analyze the performance of their MSME businesses. The information needed in analyzing the business performance of MSMEs can be seen in the financial reports prepared by these MSMEs. In practice there are still many MSME entrepreneurs who still think that the preparation of these financial reports is not very important, so that in the end these MSME entrepreneurs cannot analyze their business performance in real terms. For this reason, The Accounting Study Program, Economics and Business Faculty, Trisakti University in collaboration with The Management of  Rukun Warga (RW) 08, Kayu Putih Village, Pulo Gadung District, in East Jakarta, held a Community Service (PKM)  Program by providing training to MSME entrepreneurs in Rukun Warga (RW) 08, Kayu Putih Village, Pulo Gadung District, East Jakarta, so that these MSMEs can understand and understand the importance of compiling Financial Reports for MSMEs in accordance with applicable Financial Accounting Standards in analyzing real financial performance. The results after the implementation of the PKM were in line with expectations, where participants were very enthusiastic about asking questions about the accounting process, the concept of business entities and answering the given accounting exercise questions, where the results of the assessment obtained an average score of 62 to 73.